Industry Effects in the Dividend Initiation Decision - Huang, Wei; Paul, Donna L. (Journal of Accounting and Finance, 2024)
We examine industry effects on the likelihood and level of dividend initiations. Results suggest that firms incorporate industry expectations for dividend levels and growth into the initiation decision. They are in general less likely to initiate a dividend if dividend levels in the industry are high or growing. Firms that do initiate seek to match industry peers in initiation levels. We also find that announcement returns to dividend initiating firms are lower when more industry peers are dividend payers and when industry dividend growth is high. Together, these results provide support for an industry equilibrium dividend policy.